The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smtd.202201592
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Tough Nanostructured Hydrogels and Organogels Prepared by Polymerization‐Induced Self‐Assembly

Abstract: In nature, the hierarchical structure of biological tissues endows them with outstanding mechanics and elaborated functions. However, it remains a great challenge to construct biomimetic hydrogels with well-defined nanostructures and good mechanical properties. Herein, polymerization-induced self-assembly (PISA) is for the first time exploited as a general strategy for nanostructured hydrogels and organogels with tailored nanodomains and outstanding mechanical properties. As a proof-of-concept, PISA of BAB tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…6a). 79 To verify this, we prepared a series of multiphase hydrogels by chain-extending the bifunctional poly(ethylene glycol) (PEG) macro-CTA (molecular weight: 20 kDa) with DAAm at a target solids content of 50 wt% (Fig. 6b).…”
Section: Multiphase Hydrogels Fabricated Via Pisamentioning
confidence: 99%
See 1 more Smart Citation
“…6a). 79 To verify this, we prepared a series of multiphase hydrogels by chain-extending the bifunctional poly(ethylene glycol) (PEG) macro-CTA (molecular weight: 20 kDa) with DAAm at a target solids content of 50 wt% (Fig. 6b).…”
Section: Multiphase Hydrogels Fabricated Via Pisamentioning
confidence: 99%
“…With this strategy, a variety of tough multiphase gels, including organogels, PEG gels, and ionogels, were also produced, demonstrating its broad feasibility. 79…”
Section: Multiphase Hydrogels Fabricated Via Pisamentioning
confidence: 99%
“…The hydrophilic chains in its network structure are highly entangled and act as sliding links. The tension can be transferred to the micelle crosslinkers during the deformation process of the hydrogel, thereby dissipating energy through the reversible deformation and irreversible separation of the polymer chains and achieving toughening of the hydrogel [ 118 ]. Li et al reported highly stiff and tough protein-based hydrogels constructed by introducing chain entanglements into the hydrogel network made of folded elastomeric proteins, as shown in Figure 4 b.…”
Section: Strategies and Properties Of Tough Hydrogelsmentioning
confidence: 99%
“…To address these issues, the PISA method was developed. It can directly prepare diblock copolymer nanoparticles with controllable morphology [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , and high concentration (50 wt%), offering the advantages of simplicity, efficiency, and repeatability. With the advancement of PISA, initiation is no longer limited to thermal methods, leading to the emergence of greener and more energy-efficient initiation mechanisms and supportive methods.…”
Section: Introductionmentioning
confidence: 99%